Bioinspired design of lightweight laminated structural materials and the intralayer/interlayer strengthening and toughening mechanisms induced by the helical structure. (15th November 2021) - Zhang, Xingyuan; Luan, Yunbo; Li, Yongcun; Wang, Zhihua; Li, Zhiqiang; Xu, Feng; Guo, Zhangxin
Highlights: High-performance bionic materials with helical laminated structure was prepared. The failure mechanisms of this bioinspired materials have been analyzed. The intralayer tensile/compressive stress has crucial effect on the bearing capacity. The interlayer shear stress has vital influence on the energy absorption. Abstract: Strengthening and toughening is always the goal of lightweight structural materials. Here, a biomimetic structural material with excellent strength and toughness was designed and prepared by using carbon fiber/epoxy composite thin-layer by imitating the helical laminated structure of mantis shrimp rods, and its deformation failure and energy absorption properties were studied. During the process of deformation and failure of helical structure, there are complex intralayer and interlayer stress distribution, which have an important impact on the load transfer efficiency. As the interlaminar helix angle change, the stress distribution of intralayer and interlayer will change significantly, which may lead to complex failure forms (i.e., fiber fracture, matrix rupture, fiber–matrix debonding and spallation), and furthermore have an important influence on the bearing capacity and energy absorption of the materials. These results have positive guiding significance for the internal structure design and performance optimization of high-performance structural materials.